Preparation and characterization of chitosan—Polyethylene glycol‐polyvinylpyrrolidone‐coated superparamagnetic iron oxide nanoparticles as carrier system: Drug loading and in vitro drug release study. Issue 4 (21st March 2016) - Prabha, G.; Raj, V.
Abstract: In the present research work, the anticancer drug "curcumin" is loaded with Chitosan (CS)—polyethylene glycol (PEG)‐polyvinylpyrrolidone (PVP) (CS‐PEG‐PVP) polymer nanocomposites coated with superparamagnetic iron oxide (Fe3 O4 ) nanoparticles. The system can be used for targeted and controlled drug delivery of anticancer drugs with reduced side effects and greater efficiency. The prepared nanoparticles were characterized by Fourier transmission infrared spectroscopy (FTIR), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Curcumin drug‐loaded Fe3 O4 ‐CS, Fe3 O4 ‐CS‐ PEG and Fe3 O4 ‐CS‐PEG‐PVP nanoparticles exhibited the mean particle size in the range of 183 − 390 nm with a zeta potential value of 26 mV−41 mV as measured using Malvern Zetasizer. The encapsulation efficiency, loading capacity and in‐vitro drug release behaviour of curcumin drug‐loaded Fe3 O4 ‐CS, Fe3 O4 ‐CS‐PEG, and Fe3 O4 ‐CS‐PEG‐PVP nanoparticles were studied using UV spectrophotometer. Besides, the cytotoxicity of the prepared nanoparticles using MTT assay was also studied. The curcumin drug release was examined at different pH medium (4.5 and 7.4) and temperature (37°C and 45°C), and it was proved that the drug release depends upon the pH medium and temperature in addition to the nature of matrix. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 808–816, 2016.